Impactos que generan los abonos orgánicos edáficos en los cultivos de hortalizas - Arreaga Zambrano, Ariel Adolfo (2023)
This research work is based on the "Impacts generated by soil organic fertilizers on vegetable crops", which represents a broad and relevant perspective in food production today, since the use of these elements tends to generate significant impacts over time on the environment. This investigative project was carried out with the objective of analyzing the possible environmental impacts generated by edaphic organic fertilizers in vegetable crops. The present investigative document presented as a study component, was developed through the collection of all types of information, carrying out a detailed investigation in the different free access web pages, scientific articles, degree theses, sources and bibliographic documentation available in different digital platforms. The results of the study on the impacts generated by edaphic organic fertilizers on vegetable crops "includes the collaboration and compilation of authors, providing a comprehensive approach to the use of organic fertilizers, the different fundamental contexts were involved. Implementing sustainable and adequate agricultural practices allows reducing environmental impacts. This includes the precise and controlled application of organic fertilizers, the use of soil conservation techniques, and the implementation of water management systems that prevent contamination.